The Use of Virtual Reality in Radiology Education: Review Article Year of Publication 2010 - 2022 - Ardi Soesilo Wibowo; Edy Cahyono; Sutikno Sutikno; Dyah Rini Indriyanti; Bambang Subali; Ellianawati Ellianawati (Universitas Negeri Semarang, 2022)
Background: Advancement in the healthcare sector, the complexity of health problems and healthcare system become an additional burden for healthcare workers who have incompetence along with professional education of healthcare workers, specifically in radiology education. Virtual reality has great potential in educational learning tool development to encounter various challenges in future radiology education. Objective: To determine the scope of virtual reality and its effectiveness as an educational learning tool in radiology education. Methods: A literature review was carried out to explore articles related with application of virtual reality in radiology education by adjusting various search terms: